A simulation system of radiation field and its detection for nuclear and radiological emergency preparedness and response training. (1st June 2022) - Ji, Yunlong; Wang, Xiaoning; Zou, Yang; Li, Dawei; Zhang, Yuxin; Ning, Jing
Abstract: Appropriate training of the related personnel is one of the most important aspects in nuclear and radiological emergency preparedness and response. The use of simulation training could provide the trainees learning experience of a lifelike, hands-on scenario without associated radiation safety restrictions. In this study, we established a radiation field simulation system that includes two separate parts. For small-area radiation field simulation, a set of simulation sources and detectors was designed based on ultra wide band distance measurement technology. For large-area field simulation, a Gaussian plume model was used to simulate the dispersion of released radioactive aerosols and calculate the consequent radiation field. Also, a Global Position System positioning and wireless transmission technique was used for simulation instruments' data acquisition. This system could create a verisimilar but also safe and radiation-free environment and can be used in the training of nuclear emergency first responders, rescue teams or radiation protection personnel.